A simplified technique for nerve-sparing type III radical hysterectomy: By reorganizing their surgical sequence, surgeons could more easily identify key nerves - Kittipat Charoenkwan (2018)
Nerve-sparing radical hysterectomy was developed in an attempt to minimize complications, including bladder, colorectal, and sexual dysfunction which are associated with disruption of the pelvic autonomic nerves during resection of the parametrium. In this article, the author proposes a simple, effective technique for identification and preservation of the pelvic nerves during type III radical hysterectomy. The essential technical considerations include the sequential approach to parametrial resection, starting from the posterior part, the direct visualization of the main nerve trunks at all sites during parametrial resection, and the avoidance of direct manipulation and unnecessary dissection of the nerves. Operative outcomes of 22 patients with cervical or uterine cancer who underwent type III radical hysterectomy from August 2008 to March 2010 were reviewed. Comparing with the earlier method performed at the author's institution, the present echnique was associated with an increased proportion of patients who had a postvoid residual urine volume (PVR) under 50 mL at postoperative day 7 (55% vs 27%) and a shorter median duration before this PVR was reached (7 days vs 9 days). The systematic approach proposed in this article would make the nerve-sparing technique for radical hysterectomy more straightforward and applicable to various settings. A thorough understanding of anatomy and adequate surgical skills are always vital components of successful nervesparing radical hysterectomy.© 2010 Published by Mosby, Inc.